Adsorption of carbon dioxide using polyethyleneimine modified silica gel - Zhu, Tao; Yang, Seil; Choi, Dae Ki; Row, Kyung Ho (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2010)
To find an ideal adsorbent for carbon dioxide capture, a new polyethyleneimine modified silica gel material was synthesized with a simple procedure. Three silica gel materials with various particle sizes (15, 25 and 40-63 mu m) were prepared and functionalized with polyethyleneimine. The carbon dioxide adsorption amounts of modified silica gel and non-modified silica gel were calculated using a mass balance equation at three different temperatures (298.15, 308.15 and 318.15 K), respectively, and the influence of gas pressure and particle size on adsorption was discussed. Experimental data showed that the carbon dioxide adsorption capacity of modified silica gel was better than non-modified silica gel, and the adsorption capacity gradually decreased with increasing particle size. The smaller particle size (15 mu m) PEI modified silica gel had the largest adsorption capacity, at 298.15 K, and the adsorption amounts of various particle sizes of PEI-silica better fit the Langmuir isotherm model.
Keywords: MESOPOROUS SILICAS; CO2; IMPREGNATION; SEPARATION; CAPTURE; NITROGEN; SORBENT; REMOVAL; ACID